Preparation and detection application of CuFe2O4 / Cu / MnO2 nano-enzyme and hydrogel of CuFe2O4 / Cu / MnO2 nano-enzyme

Through the colorimetric sensing method of CuFe2O4/Cu/MnO2 nanoenzyme and DES-Aga hydrogel, the problems of low sensitivity and high cost of detection of harmful substances in the prior art are solved, and hydroquinone and glutatam are realized The high sensitivity and simplicity of peptides and nitrites provide a portable detection solution.

CN119216576APending Publication Date: 2024-12-31SHENYANG PHARMA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411292712.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing detection methods have low sensitivity, high cost and difficulty in field testing for harmful substances such as rekinetine, glutathione and nitrite, which limits their wide application in the field of biomedical science.

Method used

A colorimetric sensing method for CuFe2O4/Cu/MnO2 nanoenzyme and CuFe2O4/Cu/MnO2 nanoenzyme hydrogel based on DES-Aga was developed. Instant colorimetric detection was performed using a smartphone to achieve target substances. High sensitivity, simplicity and on-site inspection.

Benefits of technology

Accurate quantitative analysis of hydroquinone, glutathione and nitrite is achieved, providing a portable and effective detection mode, with better oxidase-like catalytic activity and stability, and reducing detection costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005045081360000121
    Figure BDA0005045081360000121
  • Figure BDA0005045081360000122
    Figure BDA0005045081360000122
  • Figure BDA0005045081360000123
    Figure BDA0005045081360000123
Patent Text Reader

Abstract

The invention belongs to the technical field of biosensors, and particularly relates to preparation and detection application of CuFe2O4 / Cu / MnO2 nano-enzyme and hydrogel of the CuFe2O4 / Cu / MnO2 nano-enzyme. The preparation method comprises the following steps: mixing Fe < 3 + >, Cu < 2 + >, anhydrous sodium acetate and ethylene glycol, reacting for 5-12 hours at the temperature of 160-200 DEG C, performing ultrasonic dissolution, adding HCl and KMnO4, continuously stirring, reacting for 5-15 hours at the temperature of 80-150 DEG C, and drying to obtain the nano-enzyme. Preparing nano-enzyme hydrogel: mixing choline chloride and lactic acid, heating and stirring to obtain a DES solution; and adding agarose and DES into the boiling acetic acid-sodium acetate buffer solution, continuously stirring, adding an aqueous solution prepared from the nano-enzyme, and cooling and solidifying to obtain the nano-enzyme hydrogel. The HQ, the GSH and the NO2 <-> are measured by a colorimetric sensing method based on the nano-enzyme and an instant colorimetric sensing method based on the hydrogel, and the methods are simple, rapid, sensitive and accurate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biosensors, and specifically relates to a CuFe2O4 / Cu / MnO2 nanozyme and a preparation method and application of a CuFe2O4 / Cu / MnO2 nanozyme hydrogel based on DES-Aga. Background Art

[0002] Hydroquinone (HQ) is an artificial additive, which is mostly used in skin care products. It can lighten pigments and whiten the skin. However, long-term use of whitening skin care products containing HQ is very harmful to skin health. Skin care products with high concentrations of HQ compounds will cause excessive pigmentation, damage the skin and even have a corrosive effect, and are carcinogenic. Therefore, sensitive and selective detection of HQ in skin care products is needed to protect human health.

[0003] In the food industry, nitrite (NO2 - ) is used as a preservative additive to preserve foods such as meat and pickles from spoilage. Despite its widespread use, it is reported to be one of the pollutants that can react with biogenic amines to produce carcinogenic N-nitroso compounds. Epidemiological studies have attributed many diseases to high concentrations of NO2 - intake, such as methemoglobinemia, gastric cancer, hypertension, pyrocytemia, congenital disabilities and spontaneous abortion. Therefore, it is necessary to develop an efficient and reliable NO2 - It is important to determine the method to ensure safe levels.

[0004] Glutathione (GSH) is a major antioxidant molecule in living cells. It is present in most forms of aerobic cells and its task is to remove reactive oxygen species (ROS) produced in cells under different circumstances. This antioxidant molecule is an important biomarker for Parkinson's disease, mitochondrial disease, oxidative stress or cardiovascular disease, and is widely studied in cancer. Under normal circumstances, reduced glutathione is the most common form of GSH in mammalian cells, and its expression in the serum of disease patients shows significant abnormalities. Therefore, its detection and quantification are of great significance in the biomedical field.

[0005] At present, a variety of methods, including chromatography, capillary electrophoresis and electrochemical methods, have been applied to the determination of the above-mentioned harmful substances and biomarkers. However, defects such as complex external environmental interference, high testing costs and difficulties in on-site testing have limited the widespread application of the above-mentioned detection methods. Therefore, it is particularly important to develop a new highly sensitive and simple on-site detection method. Summary of the invention

[0006] The present invention is based on the synthesis of a core-shell nanocomposite material (CuFe2O4 / Cu / MnO2), which is used as an artificial oxidase mimetic to rapidly catalyze the oxidation of 3,3′,5,5′-tetramethylbenzidine (TMB), with a characteristic peak appearing at 652nm and producing a unique blue compound (oxTMB), thereby developing a nanozyme-based colorimetric sensing method. Combining a smartphone with this detection mode, a more intuitive and convenient hydrogel colorimetric sensing mode is proposed, in which the hydrogel used is a CuFe2O4 / Cu / MnO2 nanozyme hydrogel based on DES-Aga. From the antioxidant properties of HQ, GSH and NO2 - Based on the diazotization characteristics of the nanozyme, the accurate quantitative analysis of the analyte was achieved and applied to the detection of target samples. This study provides new ideas for the rational design of nanozyme colorimetric sensors, and also proposes an effective portable detection mode for the quantitative analysis and real-time monitoring of harmful substances and biomarkers.

[0007] In order to achieve the above objectives, the present invention adopts the following technical solutions:

[0008] The present invention provides a core-shell CuFe2O4 / Cu / MnO2 nanozyme composite material, and the preparation method of the nanozyme composite material comprises the following steps:

[0009] (1) Fe 3+ , Cu 2+ , anhydrous sodium acetate and ethylene glycol are uniformly mixed and reacted at 160-200°C for 5-12 hours, and after cooling, the material is collected by an external magnetic field, washed and dried to obtain a CuFe2O4 / Cu composite material;

[0010] (2) The composite material is ultrasonically dissolved in deionized water, HCl and KMnO4 are added and stirred continuously, followed by reaction at 80-150°C for 5-15 hours, and after cooling, the material is collected by an external magnetic field, washed alternately with deionized water and anhydrous ethanol, and dried to obtain a core-shell CuFe2O4 / Cu / MnO2 nanozyme composite material; preferably, the temperature is 80-120°C and the reaction time is 8-12 hours.

[0011] In the above technical solution, further, the Cu in step (1) 2+ , Fe 3+ , the ratio of anhydrous sodium acetate and ethylene glycol solution is 1g: (1.5-2.5)g: (4-5)g: (20-50)mL; the Fe 3+ and Cu 2+ FeCl3·6H2O and CuSO4·5H2O were added in solid form respectively.

[0012] In the above technical solution, further, in step (1), the mixing temperature is 25-40° C., and the magnetic stirring is 1-3 h, preferably 2 h; the drying temperature is 30-100° C., and the drying time is 5-10 h.

[0013] In the above technical solution, further, in step (2), the ultrasonic time is 10 to 40 minutes, preferably 30 minutes, and the stirring time is 0.5 to 2 hours;

[0014] The CuFe2O4 / Cu, KMnO 4、 The usage ratio of HCl solution and deionized water is 1 g: (1-2) g: (0.5-1) mL: (100-300) mL.

[0015] In the above technical solution, further, in step (2), the oven drying temperature is 50-100° C., and the drying time is 5-10 h; preferably 60° C.; and the drying time in the oven is 8-12 h.

[0016] The present invention also provides a CuFe2O4 / Cu / MnO2 nanozyme hydrogel based on DES-Aga, and the preparation method of the nanozyme hydrogel comprises the following steps:

[0017] (1) mixing choline chloride and lactic acid, heating and stirring, and obtaining a uniform and transparent DES (natural deep eutectic solvent) solution;

[0018] (2) Add agarose and DES to a boiling acetic acid-sodium acetate buffer solution and stir continuously, then add an aqueous solution prepared from a core-shell CuFe2O4 / Cu / MnO2 nanozyme composite material, drop the mixed solution into a well plate, and after cooling and solidifying, obtain a CuFe2O4 / Cu / MnO2 nanozyme hydrogel based on DES-Aga; the core-shell CuFe2O4 / Cu / MnO2 nanozyme composite material is the aforementioned nanozyme composite material.

[0019] In the above technical solution, further, in step (1), the molar ratio of choline chloride to lactic acid is 1:1-1:10, the heating temperature after mixing is 50-90° C., and the stirring time is 1 to 3 hours.

[0020] In the above technical solution, further, the concentration of the acetic acid-sodium acetate buffer solution in step (2) is 0.2 mol·L -1 , pH = 4; the concentration of the aqueous solution prepared by the CuFe2O4 / Cu / MnO2 nanozyme composite material is 0.5-5 mg·mL -1 , preferably 1.0 mg·mL -1; The dosage ratio of agarose, DES, acetic acid-sodium acetate buffer solution and CuFe2O4 / Cu / MnO2 nanozyme solution in step (2) is 1g: (10-50)mL: (40-80)mL: (10-20)mL.

[0021] The present invention also provides a kit, which comprises the aforementioned CuFe2O4 / Cu / MnO2 nanozyme composite material and / or the aforementioned nanozyme hydrogel.

[0022] The present invention also provides the aforementioned CuFe2O4 / Cu / MnO2 nanozyme composite material, the aforementioned nanozyme hydrogel or the aforementioned kit in the presence of hydroquinone (HQ), glutathione (GSH) and nitrite (NO2 - ) detection; preferably, for the detection of hydroquinone (HQ) in skin care products, the detection of glutathione (GSH) in human serum, the detection of nitrite (NO2 - ) detection.

[0023] In the above technical solution, further, the application of the colorimetric sensing method based on CuFe2O4 / Cu / MnO2 nanozyme to determine HQ, GSH and NO2 - and hydrogel-based instant colorimetric sensing for determination of HQ, GSH, and NO2 - :

[0024] The method for detecting hydroquinone using the CuFe2O4 / Cu / MnO2 nanozyme composite material is as follows: TMB, nanozyme solution, HQ standard solution with different concentration gradients, and acetic acid-sodium acetate buffer are mixed and reacted at room temperature; a standard curve is drawn with the 652nm ultraviolet absorbance difference ΔA and HQ concentration, ΔA=A0-A, A is the absorbance value corresponding to the addition of different concentrations of HQ, A0 represents the absorbance value of the blank group, and the absorbance difference ΔA of the HQ solution to be tested is determined by the above method and brought into the standard curve to calculate the HQ concentration to be tested;

[0025] The method for detecting glutathione with the CuFe2O4 / Cu / MnO2 nanozyme composite material is as follows: TMB, nanozyme solution, glutathione standard solution with different concentration gradients, and acetic acid-sodium acetate buffer are mixed, and the solution is reacted at room temperature; a GSH concentration-dependent response curve is drawn by the change ΔA of the absorbance at 652nm, ΔA=A0-A, A is the absorbance value corresponding to the addition of different concentrations of GSH, A0 represents the absorbance value of the blank group, and according to the above detection method, the ΔA of the glutathione solution to be tested is measured and brought into the curve to calculate the glutathione concentration to be tested;

[0026] The method for detecting nitrite using CuFe2O4 / Cu / MnO2 nanozyme composite material is as follows: TMB, nanozyme solution, and acetic acid-sodium acetate buffer are mixed, reacted at room temperature, and different concentration gradients of NO2 are added. - The solution was reacted for another 40 min at room temperature, and the absorbance spectrum of the solution was measured. The peaks at 445 nm and 652 nm were used for NO2 - The quantitative analysis was based on the absorbance ratio (A 445 / A 652 ) and NO2 - Draw a standard curve based on the concentration, and determine the NO2 concentration to be tested according to the above detection method. - Solution, the absorbance ratio (A 445 / A 652 ) into the standard curve and calculate the NO2 to be measured - concentration;

[0027] The method for detecting hydroquinone using nanozyme hydrogel is as follows: TMB solution and HQ standard solutions of different concentrations are mixed in acetic acid-sodium acetate buffer, and then added to the nanozyme hydrogel. After reaction at room temperature, the hydroquinone is detected at 0.5-100 μmol·L -1 A series of photos were recorded by a smartphone within the range, and the grayscale of the image was identified by Image J software. The normalized color intensity (normalizedΔcolorintensity) of the difference (Δcolor intensity) with the blank group (i.e., no HQ in the system) was fitted with the HQ concentration to obtain an equation; according to the above method, the normalizedΔcolorintensity of the HQ solution to be tested was substituted into the equation to calculate the HQ concentration to be tested;

[0028] The method for detecting glutathione by nanozyme hydrogel is as follows: TMB solution and GSH standard solutions of different concentrations are mixed in acetic acid-sodium acetate buffer, and then dripped onto the nanozyme hydrogel. After reaction at room temperature, the glutathione is detected at 0.5-100 μmol·L -1 A series of photos were recorded by a smartphone within the range, and the grayscale of the image was identified by Image J software. The normalized color intensity (normalizedΔcolorintensity) of the difference Δcolor intensity with the blank group (i.e., no HQ in the system) was fitted with the HQ concentration to obtain an equation; according to the above method, the normalizedΔcolor intensity of the glutathione solution to be tested was substituted into the equation to calculate the glutathione concentration to be tested;

[0029] The method for detecting nitrite with nanozyme hydrogel is as follows: TMB solution is mixed in acetic acid-sodium acetate buffer, added dropwise to the nanozyme hydrogel, reacted at room temperature, and then different concentrations of NO2 are further added. - Solution, after 40 min of reaction, 0.2 to 250 μmol·L -1 The series of sample photos were taken by a smartphone, processed by Image J, and further converted into RGB (red, green, blue) values. The normalized Δcolor intensity was compared with NO2 - According to the above method, the concentration of NO2 - The normalized Δcolorintensity of the solution is substituted into the equation to calculate the NO2 to be measured - concentration.

[0030]

Working Principle

[0031] Based on the inhibition of oxTMB by the reducing property of HQ and GSH, the color becomes lighter, which is different from the antioxidant principle of HQ and GSH. In the timing based on the colorimetric sensing of nanozymes, different concentrations of NO2 - The addition of NO2 caused the solution to change from blue to green and then to yellow, and at the same time, the absorbance of oxTMB at 652 nm decreased and the absorbance of diazotized oxTMB at 445 nm increased. - In an acidic environment, oxTMB (-NH2 group) can be diazotized to generate diazotized oxTMB (-N≡N+). Therefore, based on the CuFe2O4 / Cu / MnO2 catalytic conversion of TMB to oxTMB, different concentrations of NO2 - It will cause oxTMB to be transformed into diazotized oxTMB to varying degrees, resulting in changes in two visible light signals, achieving NO2 - Quantitative detection of .

[0032] Hydrogel-based instant colorimetric sensing of NO2 - Concentration ranges from 0.2 to 250 μmol·L -1 The series of sample photos were taken by a smartphone and processed by Image J, and then converted into RGB (red, green, blue) values. The comparison of the three channel values ​​showed that the R channel was - The normalized color intensity is related to NO2 - The concentration is linearly fitted to obtain a linear equation to achieve quantitative detection.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The magnetic nanozyme CuFe2O4 / Cu / MnO2 synthesized by the present invention has better oxidase-like catalytic activity than other nanozymes, is more stable than natural enzymes and can be reused.

[0035] The DES-Aga hydrogel prepared by the present invention forms a cross-linked network due to polar interactions (mainly hydrogen bonds), and is more stable and more transparent in color than the Aga single-component hydrogel, and can be used as a matrix for carrying nanozymes.

[0036] With HQ, GSH and NO2 - Compared with other analytical methods, the proposed analytical method based on nanozyme CuFe2O4 / Cu / MnO2 and DES-Aga hydrogel is simple, rapid and cost-effective. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 For selective colorimetric detection of HQ, GSH and NO2 - Schematic diagram of the dual sensing platform; (a) Preparation method; (b) CuFe2O4 / Cu / MnO2 nanozyme colorimetric and DES-Aga hydrogel instant colorimetric detection of HQ and GSH; CuFe2O4 / Cu / MnO2 nanozyme colorimetric and DES-Aga hydrogel instant colorimetric detection of NO2 - ;

[0038] Figure 2 The SEM and TEM characterization images of nanozymes: (a) SEM image of CuFe2O4; (b) SEM image of CuFe2O4 / Cu; (c) SEM image of CuFe2O4 / Cu / MnO2 (200nm); (d) HRTEM image of 1μm; (e) TEM image of 200nm; (f) HRTEM image of 100nm; (g) HRTEM image of CuFe2O4 / Cu / MnO2;

[0039] Figure 3 These are the X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) of nanozymes; (a) XRD spectrum of CuFe2O4 / Cu / MnO2; (b) full XPS spectrum of CuFe2O4 / Cu / MnO2; (c) high-resolution XPS spectrum of Cu 2p; (d) high-resolution XPS spectrum of iron 2p; (e) high-resolution XPS spectrum of Mn 2p; (f) high-resolution XPS spectrum of O-1s.

[0040] Figure 4 are the magnetization curves of CuFe2O4 / Cu and CuFe2O4 / Cu / MnO2;

[0041] Figure 5 Effects of different reaction conditions on oxidase activity: (a) reaction time, (b) reaction temperature, (c) reaction system pH, (d) TMB concentration, (e) nanozyme concentration;

[0042] Figure 6 HQ determination test diagram; (a) shows different concentrations of HQ (0.1~20μmol·L -1 ) on the UV-visible absorption spectrum of the system; (b) linear fitting of HQ determination;

[0043] Figure 7 GSH determination test diagram; (a) is different GSH concentrations (0.1 ~ 25μmol·L -1 ) UV-visible absorption spectrum of the system under (b) linear fitting of GSH determination;

[0044] Figure 8 NO2 - Determination test diagram; (a) Different NO2 - Concentration (0.1~100μmol·L -1 ) UV-visible absorption spectrum of the system; (b) NO2 - Linear fit of the assay;

[0045] Fig. 9 Hydrogel colorimetric sensing test diagram for HQ, GSH and NO2-; (a) is the relationship diagram between the normalized Δcolor hydrogel strength and the HQ concentration (n=3); (b) is the relationship diagram between the normalized Δcolor hydrogel strength and the GSH concentration (n=3); (c) is the relationship diagram between the normalized Δcolor hydrogel strength and the NO2- concentration (n=3). DETAILED DESCRIPTION

[0046] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings in the embodiments of the present invention, but does not constitute any limitation to the present invention, and any limited modifications made within the scope of protection of the claims of the present invention are still within the scope of protection of the claims of the present invention.

[0047] Example 1: Preparation and characterization

[0048] 1.3525g FeCl3·6H2O, 0.625g CuSO4·5H2O, 3.0g anhydrous sodium acetate and 30mL ethylene glycol were accurately weighed and placed in a 100mL stoppered conical flask. After magnetic stirring for 2h at 30℃ to mix all reagents evenly, they were transferred to a 50mL autoclave and reacted at 200℃ for 12h. After cooling to room temperature, the materials were collected by magnetic interaction with the external magnetic field (such as using magnet adsorption), and washed with deionized water and anhydrous ethanol for 5 times respectively, and placed in a 60℃ oven for 8h to obtain CuFe2O4 / Cu. (At the same time, 0.375g CuFe2O4 / Cu was accurately weighed and placed in a 250mL three-necked flask, 1.5g FeCl3·6H2O and 150mL deionized water were added, and CuFe2O4 was obtained by mechanical stirring for 12h.)

[0049] Accurately weigh 0.15g CuFe2O4 / Cu into a 100mL three-necked flask and accurately measure 30mL deionized water for 30min ultrasonic dispersion to make it uniform. Add 0.6mL HCl and 0.27g KMnO4 under continuous stirring, continue stirring for 1h, transfer to a 50mL autoclave, and react at 100℃ for 12h. After cooling to room temperature, collect the material using an external magnetic field, wash it alternately with deionized water and anhydrous ethanol for 5 times, and then dry it in a 60℃ oven for 8h to obtain CuFe2O4 / Cu / MnO2.

[0050] Synthesis of DES: Choline chloride and lactic acid were added into a 50 mL conical flask at a molar ratio of 1:1 and stirred at 60 °C for 1 h to obtain a homogeneous transparent solution.

[0051] Synthesis of CuFe2O4 / Cu / MnO2 nanozyme hydrogel based on DES-Aga: 0.15 g agarose was accurately weighed and added into 10 mL boiling acetic acid-sodium acetate buffer solution (0.2 mol·L -1 , pH = 4), add 4.5 mL of DES under constant stirring. Accurately weigh a certain amount of CuFe2O4 / Cu / MnO2 nanoenzyme and add deionized water to a concentration of 1.0 mg mL -1 2.5 mL of the solution was precisely measured and dropped into the mixed solution and stirred evenly; 500 μL of the solution was dropped into the wells of a 24-well plate, and after cooling and solidification, the CuFe2O4 / Cu / MnO2 nanozyme hydrogel based on DES-Aga was prepared.

[0052] Various optical characterization results are as follows:

[0053] Figure 2(a-c) show the SEM images of CuFe2O4, CuFe2O4 / Cu, and CuFe2O4 / Cu / MnO2 composites. CuFe2O4 and CuFe2O4 / Cu are composed of nanospheres assembled from small nanoparticles without aggregation. Figure 2 b It can be seen that CuFe2O4 / Cu presents larger particles due to the presence of Cu. CuFe2O4 / Cu / MnO2 presents corolla-shaped and layered microspheres. This porous microsphere structure may be due to the reaction of KMnO4 with HCl to generate a large number of atomic nuclei, which are captured by the CuFe2O4 / Cu particles dispersed in the solution and grow around their surfaces, wrapping them into a spherical structure. At the same time, the CuFe2O4 / Cu particles not encapsulated by MnO2 are dispersed around the spherical structure.

[0054] Figure 2 (df) are TEM images of CuFe2O4 / Cu / MnO2 of different sizes, which confirm the core-shell structure of nano-sized CuFe2O4 / Cu / MnO2. CuFe2O4 / Cu is the core and the shell is the grown MnO2 nanosheets with wrinkles, which is consistent with the SEM image. HRTEM shows that CuFe2O4 / Cu / MnO2 has a distinct lattice stripe structure, in which the 0.20nm spacing belongs to the (311) crystal plane of CuFe2O4, the lattice spacing of 0.24nm may correspond to the (400) crystal plane of CuFe2O4 or the (111) crystal plane of Cu0, and the stripe of d=0.35nm is consistent with the (002) crystal plane of MnO2. The results confirm the successful synthesis of CuFe2O4 / Cu / MnO2.

[0055] The phase structure and composition of the obtained catalyst were characterized by XRD technique. Figure 3As shown in a, in the CuFe2O4 diffraction peak spectrum, the diffraction peaks at 2θ=18.28°, 30.1°, 35.4°, 37.0°, 43.0°, 53.4°, 56.9° and 62.5° can be attributed to the (111), (220), (311), (222), (400), (422), (511) and (440) crystal planes of CuFe2O4 (JCPDS No.73-2317). In the CuFe2O4 / Cu spectrum, in addition to some characteristic peaks corresponding to CuFe2O4, the peaks at 2θ=43.4°, 50.5° and 74.2° correspond to the (111), (200) and (220) planes of metal Cu0 (JCPDS No.85-1326). In the CuFe2O4 / Cu / MnO2 spectrum, in addition to the corresponding characteristic peaks, the diffraction peaks at 12.6°, 18.1°, 25.5°, 36.4°, 57.1° and 66.0° can match the (110), (200), (220), (400), (501) and (002) crystal planes of MnO2 (JCPDS No.72-1982). From the results, it can be observed that CuFe2O4 and CuO coexist in the prepared CuFe2O4 / Cu sample. In CuFe2O4 / Cu / MnO2, due to the surface coating of MnO2, some CuO characteristic peaks are covered, and the corresponding MnO2 characteristic peaks appear at the same time, indicating that the CuFe2O4 / Cu / MnO2 composite material was successfully prepared by a simple two-step solvothermal method.

[0056] The constituent elements, valence states, and chemical bonding of CuFe2O4 / Cu / MnO2 were analyzed using X-ray photoelectron spectroscopy (XPS). Figure 3 The XPS full scan spectrum shown in b shows that CuFe2O4 / Cu / MnO2 is composed of five elements: C, Cu, Fe, Mn and O. The two main peaks of the Cu 2p spectrum at 953.28 and 934.28 eV are derived from the Cu 2p1 / 2 and Cu 2p3 / 2 spin orbits, of which the fitted 925.5 and 932.5 eV can be identified as Cu0, and 954.9 and 934.9 eV can be identified as Cu 2+ ( Figure 3 c). Meanwhile, the satellite peak at 945.98 eV corresponds to Cu 2+ The Fe 2p spectrum can also be fitted to 6 peaks, Fe 3+ This can be verified by the peaks at 726.1 and 711.3 eV and the satellite signal at 719.5 eV, while Fe 2+ The presence of can be verified by the peaks at 723.9 and 709.9 eV ( Figure 3d). The two peaks at 653.3 and 641.6 eV correspond to the Mn 2p1 / 2 and Mn 2p3 / 2 peaks, while the peaks at 653.9 and 642.9 eV correspond to the Mn 4+ , 652.6 and 641.4 eV corresponding to Mn 3+ , indicating that the formation of MnO2 ( Figure 3 e). In the O 1s spectrum, there are three fitting peaks at 532.5, 530.4 and 529.1 eV, which are attributed to the hydroxyl groups on the surface of CuFe2O4 / Cu / MnO2, the lattice oxygen of CuFe2O4 and the oxygen in the metal oxide (Mn-O-Mn) ( Figure 3 f). The results indicate that the Cu, Fe, and Mn elements contain more than one valence state in their bonding, which is beneficial for the electron transfer in the subsequent enzyme catalysis process, and the hydroxyl groups on the surface of CuFe2O4 / Cu / MnO2 may be the active sites for the generation of hydroxyl radicals and the oxidative decomposition of organic matter in the catalytic process.

[0057] Figure 4 The magnetic properties of CuFe2O4 / Cu and CuFe2O4 / Cu / MnO2, the products of the two steps of synthesis, are evaluated by hysteresis loop test (VSM). It can be seen from the figure that the magnetization curve shows a symmetrical S-type. The maximum saturation magnetization of CuFe2O4 / Cu is 58.46emu·g-1, while the maximum saturation magnetization of CuFe2O4 / Cu / MnO2 is 19.93emu·g-1. -1 , which is 38.53emu·g lower than that of CuFe2O4 / Cu -1 , probably due to the non-magnetic MnO2 coating on the outside. From the results, the synthesized CuFe2O4 / Cu / MnO2 has superparamagnetism and can be easily and quickly separated from the sample solution in the presence of an external magnetic field. It can also be observed from the inset that the CuFe2O4 / Cu / MnO2 material can be evenly dispersed in the solution by shaking and can be attached to the bottle wall by magnet adsorption, thus proving its potential for recovery by an external magnetic field.

[0058] Example 2: Optimization of detection conditions

[0059] The basis for condition optimization is the enzymatic activity of nanozymes. Usually, based on the absorption peak of TMB oxidized to blue product oxTMB by nanozymes at 652 nm, UV-visible spectroscopy is used to study the catalytic activity of oxidase-like enzymes. The specific operation process is as follows: 10 μL CuFe2O4 / Cu / MnO2 nanozyme suspension (1.0 mg mL -1 )、10μLTMB(10mmol·L -1 ) Add acetic acid-sodium acetate buffer solution (0.2 mol·L -1, pH = 4), the system was kept at 1 mL and vortexed to mix, and then incubated at room temperature (20° C.) for 8 min. Then, the absorbance of oxidized TMB (oxTMB) at 652 nm was tested by UV-vis.

[0060] Firstly, the incubation time of the catalytic system was studied ( Figure 5 a) When measuring the absorbance at different reaction times, it can be observed that the longer the incubation time, the more complete the reaction. After 8 minutes of incubation, the reaction tends to be stable, indicating that TMB in the system is almost completely catalyzed by the nanozyme to oxTMB and reaches saturation. Therefore, 8 minutes is selected as the optimal incubation time.

[0061] In addition, the influence of common nanozyme activity influencing factors (temperature and pH) on CuFe2O4 / Cu / MnO2 nanozyme composite materials was investigated. Figure 5 (b,c) It can be seen that the activity of the material gradually decreases at 20-65℃, and the catalytic ability is strongest at room temperature (20℃), but even if the temperature rises to 65℃, it can still maintain a certain catalytic activity, indicating that the material has a certain ability to withstand high temperatures. The pH shows a trend of increasing and then decreasing, reaching the maximum at pH = 4, but still retains about 50% activity under acidic and neutral conditions, indicating that the performance of the CuFe2O4 / Cu / MnO2 nanocomposite material is relatively stable and has a certain ability to withstand high temperatures and pH. In subsequent experiments, room temperature (20℃) conditions were selected in pH = 4 buffered salt solution.

[0062] In addition, the concentrations of substrate (TMB) and catalytic material (CuFe2O4 / Cu / MnO2 nanozyme) in the system were further optimized so that the absorbance of the system was within the appropriate range for UV-vis detection ( Figure 5 (d, e)). The TMB concentration in the system is 0.02-0.1 mmol·L -1 The absorbance of the solution gradually increased within the range of 0.1mmol·L -1 The absorbance of the solution remained stable when the concentration was increased, indicating that the concentration of the catalytic material was fixed and the substrate concentration was 0.1 mmol·L -1 The catalytic equilibrium is reached when the substrate concentration is increased. Further increasing the substrate concentration cannot completely react and will cause some waste. Therefore, 0.1mmol·L -1 is the concentration of substrate TMB. However, the reaction degree of the system shows a trend of increasing with the increase of nanozyme concentration. In order to save materials and achieve the purpose of appropriate absorbance, 10 μg mL -1 Nanozyme concentration was used for subsequent experimental steps. Based on the above results, 10 μg mL -1 Nanozymes in a system with a pH of 4.0 and a concentration of 0.1 mmol·L -1The TMB was reacted at 20°C for 8 min, at which time the analytical performance of the method reached the optimal level.

[0063] Example 3: HQ, GSH and NO2 - Analytical performance

[0064] 1. Nanozyme-based colorimetric sensing for determination of HQ, GSH and NO2 - :

[0065] (1) The specific steps of HQ determination are as follows: add 10 μL TMB (10 mmol·L -1 ), 10 μL nanozyme solution (1.0 mg mL -1 ), 10 μL HQ standard solution of different concentrations, acetic acid-sodium acetate buffer (0.2 mol·L -1 , pH = 4) after being shaken thoroughly, the mixed solution was reacted at room temperature for 8 minutes. In addition, the different absorbance measurements of the final solution were monitored by UV-vis. Finally, a standard curve was drawn with the absorbance difference ΔA and HQ concentration (ΔA = A0-A, where A represents the absorbance value corresponding to the addition of different concentrations of HQ to the system, and A0 represents the absorbance value of the blank group, that is, there is no HQ in the system.)

[0066] According to the above detection method, add 10 μL of HQ solution of the concentration to be tested, bring the measured absorbance difference ΔA into the standard curve, and calculate the concentration value to be tested.

[0067] When HQ of different concentrations was added into the reaction system, it was observed that the absorbance of the final solution was directly related to the HQ concentration. Figure 6 a shows the relationship between the two, with the coordinates being wavelength, HQ concentration and ΔA(A0-A), where A0 is the absorbance without HQ addition and A is the absorbance after adding different concentrations of HQ. Figure 6 b is the linear fitting diagram of HQ with a detection concentration range of 0.1 to 20 μmol·L -1 The linear regression equation obtained was y = 0.0172x + 0.0159, and the correlation coefficient R2 was 0.9955. The limit of detection (LOD) was calculated as 3 times the standard deviation (σ) divided by the slope (k), where σ is the standard deviation obtained from the blank measurement (n = 11) and k is the slope of the obtained calibration curve. The obtained LOD was 0.01 μmol·L -1 .

[0068] (2) The specific steps of GSH determination are as follows: 10 μL TMB (10 mmol·L) was added to each centrifuge tube. -1 ), 10 μL nanozyme solution (1.0 mg mL -1), 10 μL of glutathione standard solution of different concentrations, acetic acid-sodium acetate buffer (0.2 mol·L -1 , pH = 4) after being shaken thoroughly, the mixed solution was reacted at room temperature for 8 minutes. The GSH concentration-dependent response curve was drawn by the change in absorbance at 652nm (ΔA). (ΔA = A0-A, where A represents the absorbance value corresponding to the addition of different concentrations of GSH to the system, and A0 represents the absorbance value of the blank group, that is, there is no GSH in the system.)

[0069] According to the above detection method, 10 μL of glutathione solution of the concentration to be tested was added, and the change in absorbance at 652 nm (ΔA) was brought into the standard curve to calculate the concentration to be tested.

[0070] Figure 7 The visible spectrum of GSH and the corresponding linear fitting diagram are shown in Figure 2. The absorbance response of GSH is in the range of 0.1-25 μmol·L -1 The linearity was good within the range, and it gradually decreased with the increase of GSH concentration. Therefore, ΔA(A0-A) was used to linearly fit the GSH concentration, and the linear equation y=0.0151x+0.0954(R2=0.9959) was obtained. The detection limit (LOD) was calculated using the following formula: LOD=3σ / k, where σ is the standard deviation obtained from 11 blank measurements, and k is the slope of the calibration curve in the linear concentration range. The LOD of GSH was calculated to be 0.05μmol·L -1 Therefore, the present method provided satisfactory analytical performance with a lower detection limit.

[0071] (3) Add 10 μL TMB (10 mmol·L) to each centrifuge tube. -1 ), 10 μL nanozyme solution (1.0 mg mL -1 ), acetic acid-sodium acetate buffer (0.2 mol·L -1 , pH = 4). After sufficient shaking, the mixed solution was reacted at room temperature for 8 min. Subsequently, 10 μL of different concentrations of NO2 - After reacting for another 40 min at room temperature, the absorbance spectrum of the solution was measured, and the peaks at 445 nm and 652 nm were used for NO2 - Quantification of absorbance ratio (A 445 / A 652 ) and NO2 - The above experiments were repeated three times.

[0072] According to the above detection method, add 10 μL of NO2 - Solution, the absorbance ratio (A 445 / A 652) into the standard curve and calculate the concentration to be tested.

[0073] Based on NO2 - The detection principle is designed for NO2 - Quantitative detection in the visible region. Figure 8 In the A652, along with NO2 - The increase of A445 slightly decreased with the increase of NO2 - The absorbance ratio (A445 / A652) was 0.1-100 μmol·L -1 With NO2 - The concentration showed good linearity and the equation y = 0.0132x + 0.1207 (R2 = 0.9969) was obtained. The detection limit (LOD) was calculated to be 0.02 μmol·L according to 3σ / k (σ is the standard deviation obtained from 11 blank determinations, k is the slope of the calibration curve in the linear concentration range). -1 The obtained linear range and detection limit meet the 30mg·kg stipulated by the Chinese national standard. -1 Residue limit requirements.

[0074] 2. Hydrogel-based instant colorimetric sensing for determination of HQ, GSH and NO2 - :

[0075] In order to verify the feasibility of the fabricated hydrogel sensor, three analytes, HQ, GSH and NO2 - Tests were carried out.

[0076] The specific determination process of HQ is as follows: 50 μL TMB solution and 50 μL HQ standard solution of different concentrations are mixed in 400 μL acetic acid-sodium acetate buffer (0.2 mol·L -1 , pH = 4) and then dripped onto the nanozyme hydrogel. After reacting at room temperature for 20 min, the images of the hydrogel were recorded by a smartphone, and the color information was further analyzed using a color processing application (Image J) for HQ quantitative determination.

[0077] The specific determination process of GSH is as follows: 50 μL TMB solution and 50 μL GSH standard solution of different concentrations are mixed in 400 μL acetic acid-sodium acetate buffer (0.2 mol·L -1 , pH = 4) and dripped onto the nanozyme hydrogel. After reacting at room temperature for 20 min, the images of the hydrogel were recorded by a smartphone, and the image analysis was performed using a color processing application (Image J) to identify the grayscale value for quantitative determination of GSH.

[0078] NO2 - The specific determination process is as follows: Use multicolor reading to measure NO2- Smartphone-assisted visual measurement was performed. First, 50 μL of TMB solution was mixed in 400 μL of acetic acid-sodium acetate buffer (0.2 mol·L -1 , pH = 4) and dripped onto the nanozyme hydrogel. After reacting at room temperature for 20 min, 50 μL of different concentrations of NO2 were further added. - The solution was shaken. After 40 min, the images of the hydrogels were recorded by smartphones, and the RGB values ​​of the photos were identified by the mobile application Image J. The NO2 - The concentrations were fitted linearly.

[0079] The detection of HQ is in the range of 0.5-100 μmol·L -1 A series of photos were recorded by a smartphone within the range, and the grayscale of the images was identified by ImageJ software. The normalized color intensity (normalized Δcolor intensity) of the difference (Δcolor intensity) with the blank group (i.e., no HQ in the system) was fitted with the HQ concentration to obtain the equation y = 0.0086x + 0.1834 (R2 = 0.9901) ( Fig. 9 a). The limit of detection (LOD) was calculated using 3σ / k, where σ is the standard deviation of the blank assay (n=11) and k is the slope of the calibration curve. The LOD for HQ was calculated to be 0.15 μmol·L -1 According to the above method, the normalized Δcolor intensity of the HQ solution to be tested is substituted into the equation to calculate the HQ concentration to be tested.

[0080] The determination of GSH is similar to that of HQ. The color intensity after normalization is between 0.5 and 100 μmol·L -1 The concentration of GSH showed a good linear relationship within the range, y = 0.0093x + 0.0806 (R2 = 0.9929) ( Fig. 9 b) The calculated LOD is 0.13 μmol·L -1 According to the above method, the normalized Δcolor intensity of the GSH solution to be tested is substituted into the equation to calculate the GSH concentration to be tested.

[0081] NO2 - Concentration ranges from 0.2 to 250 μmol·L -1 The series of sample photos were taken by a smartphone and processed by Image J, and then converted into RGB (red, green, blue) values. The comparison of the three channel values ​​showed that the R channel was - The concentration is linear. Therefore, the normalized color intensity is compared with NO2- The linear fitting of the concentration was performed, and the result was y = 0.0032x + 0.1631, R2 = 0.9920, and LOD was 0.11 μmol·L -1 ( Fig. 9 c) Compared with the established nanozyme visible light colorimetric sensor, the linear range is wider and the detection limit is slightly higher, but it is easy to operate and flexible and portable. - The normalized Δcolor intensity of the solution is substituted into the equation to calculate the NO2 - concentration.

[0082] Example 4: Actual sample analysis

[0083] In order to verify the practicality of the established HQ, GSH and NO2- detection methods, lotion and cream samples with whitening effect, human serum samples, pickles and sausage samples were used. Skin care products and food samples were purchased from local supermarkets, and human serum samples were provided by the First Affiliated Hospital of Jilin University. Three different standard concentrations of the analytes were spiked respectively, and the actual sample recovery rate was studied by the standard addition method.

[0084] Accurately weigh 0.5 g of the purchased whitening lotion and whitening cream, place them in a 50 mL conical flask, add 20 mL of PBS buffer (0.1 mol·L -1 , pH = 7) was ultrasonicated for 30 min, and the supernatant was collected by centrifugation and filtered through a 0.22 μm filter membrane for later use.

[0085] The human serum samples were centrifuged at 10000 rpm for 10 min, and the supernatant was collected and diluted 1-fold for later use.

[0086] The purchased food samples were crushed with a wall-breaking machine, and 1 g was accurately weighed and placed in a 50 mL conical flask. 3 mL of 5% borax solution and 30 mL of ultrapure water (70 ° C) were added. After soaking in a boiling water bath for 15 min, the mixture was cooled to room temperature, and then 1 mL of potassium ferrocyanide solution (0.106 g mL -1 ) and 1 mL of zinc acetate solution (0.22 g mL -1 ) and shaken for 30 min. Finally, the supernatant was extracted by high-speed centrifugation and filtered through a 0.22 μm filter membrane for subsequent measurements.

[0087] Then select three different concentrations of HQ, GSH and NO2, low, medium and high respectively. - The standard solution was added to these real sample solutions for measurement. The specific steps were as follows: “Nanozyme-based colorimetric sensing analysis method for HQ, GSH and NO2 - Determination of HQ, GSH and NO2 -The determination was carried out as described in "Measurement of

[0088] The results are summarized in Table 1, Table 2, and Table 3. The results show that HQ was not detected in whitening lotions and creams. The average recovery rate of lotions was between 94.1% and 104.3%, with an RSD of less than 8.1%; the average recovery rate of creams was between 99.3% and 109.6%, with an RSD of less than 7.7%. After converting the dilution multiple, it was found that 416 μmol·L of GSH was detected in human serum. -1 The GSH content in normal healthy human serum is 400-1200 μmol·L -1 The amount measured in this test is consistent with it, with an average recovery rate between 90.8-115.0% and RSD less than 8.4%. - The content was calculated to be 26 μmol·L -1 The average recovery rate was between 89.7% and 94.6%, and the RSD was less than 7.8%. - The content was calculated to be 26 μmol·L -1 The average recovery rate is between 102.2-115.5%, and the RSD is less than 8.5%. According to the Chinese national standard, the residual amount shall not exceed 30 mg kg -1 The detection amount in this test did not exceed the limit standard, proving that the nanozyme colorimetric sensing platform achieved satisfactory accuracy in HQ, GSH and NO2 - It has practical application value in the determination of

[0089] Table 1 Detection of actual sample HQ based on nanozyme colorimetric sensing platform

[0090]

[0091] Table 2 Actual sample GSH detection based on nanozyme colorimetric sensing platform

[0092]

[0093] Table 3 Actual sample NO2 based on nanozyme colorimetric sensing platform - Detection

[0094]

[0095]

[0096] In the actual sample testing of hydrogel, the standard addition method was used to evaluate the hydrogel colorimetric determination of HQ, GSH and NO2 -The data in Table 4, Table 5 and Table 6 show that GSH was not detected in whitening lotion and cream samples. The average recovery rate of HQ lotion was between 100.0-113.1%, with an RSD of less than 8.6%; the average recovery rate of cream was between 90.1-107.8%, with an RSD of less than 7.0%. The detected amount multiplied by the dilution factor can be calculated to obtain a GSH content of 421 μmol·L in the healthy human serum sample used. -1 The average recovery rate was between 101.6% and 106.6%, and the RSD was less than 3.5%. By converting the dilution multiple, it can be seen that the NO2 - The content is 26μmol·L -1 The average recovery rate was between 89.7% and 94.6%, and the RSD was less than 7.8%. - The content was converted to 26 μmol·L -1 The average recovery rate was between 102.2% and 115.5%, and the RSD was less than 8.5%. The test results were comparable to those of the prepared nanozyme colorimetric sensor. This proves that the hydrogel kit can also achieve sensitive and accurate detection of the components to be tested in real samples.

[0097] Table 4 Actual sample HQ detection based on the hydrogel colorimetric sensing platform

[0098]

[0099] Table 5 Actual sample GSH detection based on the hydrogel colorimetric sensing platform

[0100]

[0101] Table 6 Actual sample NO2 based on hydrogel colorimetric sensing platform - Detection

[0102]

[0103] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and those skilled in the art can apply all improvements and modifications made based on the disclosure of the present invention without departing from the scope of the present invention.

Claims

1. A core-shell CuFe2O4 / Cu / MnO2 nanozyme composite material, characterized in that: The preparation method of the nanoenzyme composite material comprises the following steps: (1) Fe 3+ , Cu 2+ , anhydrous sodium acetate and ethylene glycol are uniformly mixed and reacted at 160-200°C for 5-12 hours. After cooling, the material is collected by an external magnetic field, washed and dried to obtain a CuFe2O4 / Cu composite material; (2) The composite material was ultrasonically dissolved in deionized water, HCl and KMnO4 were added and stirred continuously, followed by reaction at 80-150°C for 5-15 hours. After cooling, the material was collected by an external magnetic field, washed alternately with deionized water and anhydrous ethanol, and dried to obtain a core-shell CuFe2O4 / Cu / MnO2 nanozyme composite material.

2. The nanozyme composite material according to claim 1, characterized in that: Step (1) Cu 2+ , Fe 3+ , the ratio of anhydrous sodium acetate and ethylene glycol solution is 1g: (1.5-2.5)g: (4-5)g: (20-50)mL; the Fe 3+ and Cu 2+ FeCl3·6H2O and CuSO4·5H2O were added in solid form respectively.

3. The nanozyme composite material according to claim 1, characterized in that: The usage ratio of CuFe2O4 / Cu, KMnO4, HCl solution and deionized water in step (2) is 1g: (1-2)g: (0.5-1)mL: (100-300)mL.

4. The nanozyme composite material according to claim 1, characterized in that: In step (1), the mixing temperature is 25-40° C., the magnetic stirring is 1-3 h, the drying temperature is 30-100° C., and the drying time is 5-10 h. In step (2), the ultrasonic time is 10-40 min, the stirring time is 0.5-2 h, the oven drying temperature is 50-100° C., and the drying time is 5-10 h.

5. A CuFe2O4 / Cu / MnO2 nanozyme hydrogel based on DES-Aga, characterized in that: The preparation method of the nanoenzyme hydrogel comprises the following steps: (1) mixing choline chloride and lactic acid, heating and stirring, and obtaining a DES (natural deep eutectic solvent) solution; (2) Add agarose and DES to a boiling acetic acid-sodium acetate buffer solution and stir continuously, then add an aqueous solution prepared from a core-shell CuFe2O4 / Cu / MnO2 nanozyme composite material, and after cooling and solidification, obtain a CuFe2O4 / Cu / MnO2 nanozyme hydrogel based on DES-Aga; the core-shell CuFe2O4 / Cu / MnO2 nanozyme composite material is the nanozyme composite material according to any one of claims 1 to 4.

6. The CuFe2O4 / Cu / MnO2 nanozyme hydrogel based on DES-Aga as claimed in claim 5, characterized in that In step (1), the molar ratio of choline chloride to lactic acid is 1:1-1:10, the heating temperature after mixing is 50-90° C., and the stirring time is 1-3 hours.

7. The CuFe2O4 / Cu / MnO2 nanozyme hydrogel based on DES-Aga as claimed in claim 5, characterized in that The concentration of the acetic acid-sodium acetate buffer solution in step (2) is 0.2 mol·L -1 , pH = 4; the concentration of the aqueous solution prepared by the CuFe2O4 / Cu / MnO2 nanozyme composite material is 0.5-5 mg·mL -1 ; The dosage ratio of agarose, DES, acetic acid-sodium acetate buffer solution and CuFe2O4 / Cu / MnO2 nanozyme solution in step (2) is 1g: (10-50)mL: (40-80)mL: (10-20)mL.

8. A kit, characterized in that: The kit comprises the CuFe2O4 / Cu / MnO2 nanozyme composite material according to any one of claims 1 to 5 and / or the nanozyme hydrogel according to any one of claims 6 to 8.

9. The CuFe2O4 / Cu / MnO2 nanozyme composite material according to any one of claims 1 to 4, the nanozyme hydrogel according to any one of claims 5 to 7, or the kit according to claim 9 in the presence of hydroquinone (HQ), glutathione (GSH) and nitrite (NO2 - ) detection; preferably, for the detection of hydroquinone (HQ) in skin care products, the detection of glutathione (GSH) in human serum, the detection of nitrite (NO2 - ) detection.

10. The use according to claim 9, characterized in that: The application is based on the colorimetric sensing method of CuFe2O4 / Cu / MnO2 nanozyme to determine HQ, GSH and NO2 - and hydrogel-based instant colorimetric sensing for determination of HQ, GSH, and NO2 - : The method for detecting hydroquinone using the CuFe2O4 / Cu / MnO2 nanozyme composite material is as follows: TMB, nanozyme solution, HQ standard solution with different concentration gradients, and acetic acid-sodium acetate buffer are mixed and reacted at room temperature; a standard curve is drawn with the 652nm ultraviolet absorbance difference ΔA and HQ concentration, ΔA=A0-A, A is the absorbance value corresponding to the addition of different concentrations of HQ, A0 represents the absorbance value of the blank group, and the absorbance difference ΔA of the HQ solution to be tested is determined by the above method and brought into the standard curve to calculate the HQ concentration to be tested; The method for detecting glutathione with the CuFe2O4 / Cu / MnO2 nanozyme composite material is as follows: TMB, nanozyme solution, glutathione standard solution with different concentration gradients, and acetic acid-sodium acetate buffer are mixed, and the solution is reacted at room temperature; a GSH concentration-dependent response curve is drawn by the change ΔA of the absorbance at 652nm, ΔA=A0-A, A is the absorbance value corresponding to the addition of different concentrations of GSH, A0 represents the absorbance value of the blank group, and according to the above detection method, the ΔA of the glutathione solution to be tested is measured and brought into the curve to calculate the glutathione concentration to be tested; The method for detecting nitrite using CuFe2O4 / Cu / MnO2 nanozyme composite material is as follows: TMB, nanozyme solution, and acetic acid-sodium acetate buffer are mixed, reacted at room temperature, and different concentration gradients of NO2 are added. - The solution was reacted for another 40 min at room temperature, and the absorbance spectrum of the solution was measured. The peaks at 445 nm and 652 nm were used for NO2 - The quantitative analysis was based on the absorbance ratio (A 445 / A 652 ) and NO2 - Draw a standard curve based on the concentration, and determine the NO2 concentration to be tested according to the above detection method. - Solution, the absorbance ratio (A 445 / A 652 ) into the standard curve and calculate the NO2 to be measured - concentration; The method for detecting hydroquinone using nanozyme hydrogel is as follows: TMB solution and HQ standard solutions of different concentrations are mixed in acetic acid-sodium acetate buffer, and then added to the nanozyme hydrogel. After reaction at room temperature, the hydroquinone is detected at 0.5-100 μmol·L -1 A series of photos were recorded by a smartphone within the range, and the grayscale of the image was identified by Image J software. The normalized Δcolor intensity after the difference Δcolorintensity with the blank group was fitted with the HQ concentration to obtain an equation; according to the above method, the normalized Δcolor intensity of the HQ solution to be tested was substituted into the equation to calculate the HQ concentration to be tested; The method for detecting glutathione by nanozyme hydrogel is as follows: TMB solution and GSH standard solutions of different concentrations are mixed in acetic acid-sodium acetate buffer, and then dripped onto the nanozyme hydrogel. After reaction at room temperature, the glutathione is detected at 0.5-100 μmol·L -1 A series of photos were recorded by a smartphone within the range, and the grayscale of the image was identified by Image J software. The normalized color intensity of the difference Δcolor intensity from the blank group (i.e., no HQ in the system) was fitted with the HQ concentration to obtain an equation; according to the above method, the normalized Δcolor intensity of the glutathione solution to be tested was substituted into the equation to calculate the glutathione concentration to be tested; The method for detecting nitrite with nanozyme hydrogel is as follows: TMB solution is mixed in acetic acid-sodium acetate buffer, added dropwise to the nanozyme hydrogel, reacted at room temperature, and then different concentrations of NO2 are further added. - Solution, after 40 min of reaction, 0.2 to 250 μmol·L -1 The series of sample photos were taken by a smartphone, processed by Image J, and further converted into RGB (red, green, blue) values. The normalized Δcolor intensity was compared with NO2 - According to the above method, the concentration of NO2 - The normalized Δcolor intensity of the solution is substituted into the equation to calculate the NO2 - concentration.